Pengaruh Brand Ambassador dan Citra Merek terhadap Keputusan Pembelian Produk Kosmetik di Tegal - Muhamad Andi Budiyanto; Deddy Prihadi; Nabila Mutia Syahda (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study aims to analyze the influence of brand ambassadors and brand image on cosmetic product purchase decisions in Tegal. In the increasingly competitive cosmetics industry, companies utilize celebrities and influencers to build consumer trust and strengthen brand image to drive purchase decisions. This research employs a quantitative approach using Structural Equation Modeling (SEM) and analyzes data from 80 cosmetic product users in Tegal. The findings indicate that brand ambassadors have a positive and significant impact on purchase decisions, as they create emotional connections and enhance consumer trust in the product. Additionally, brand image plays a crucial role in strengthening consumer loyalty, ultimately increasing purchase intention. The study also reveals that the combination of brand ambassadors and brand image has a stronger influence than when considered individually. The conclusion of this study emphasizes that marketing strategies based on brand ambassadors and brand image are key factors in enhancing the competitiveness of the cosmetics industry. The implications suggest that cosmetic companies should select brand ambassadors that align with their brand values and consistently reinforce their brand image to increase customer loyalty and expand market share in a competitive environment